POWER IMBALANCE BETWEEN THOSE UNDER JURISDICTION AND THE NECESSARY STATE PROTECTION: AN ANALYSIS OF ENVIRONMENTAL MEDIATION IN THE LIGHT OF THE 2015 BRAZILIAN PROCEDURAL CODE - Barros, Ana Meire Vasconcelos (2023)
This paper analyses a possible power imbalance between the parties subjected to the mediation of environmental law conflicts in Brazil, in order to draw on the need for State protection in the context of environmental mediation, in the terms authorized by the new Brazilian Civil Procedural Code (CPC), enacted by Law n. 13.105/2015 and into force since March 2016. That Code enacts specific principles, including the Principle of the Governmental Promotion of Consensual Solution to Conflicts, and the postulates regarding self-composition, besides establishing the will of the parties as a value to be defended by the law. Nevertheless, it does not promote a more radical break with the old Brazilian CPC. Regarding environmental mediation, the benefits achievable are equivalent to those often achieved by mediation in general: improvement of the access to justice, mobility, empowerment of the parties, and effectiveness of the agreed solutions. However, it is noteworthy that the complicating factors and risks here are clearly larger than in other branches of law. Environmental conflicts have coverage, temporal continuity, material implications and richness of meanings that hinder their delimitation. The hypotheses of this study were investigated by means of a bibliographical research. We concluded that in the context of environmental conflicts, the possibility of inequality among the parties involved in mediations constitute a risk to the effectiveness of the solutions mediated.